2022
DOI: 10.1155/2022/5559151
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of the Volatile Oils from Caoguo-4 Decoction in Regulating Spleen Deficiency Diarrhea by Adjusting Intestinal Microbiota

Abstract: Background. The Caoguo-4 decoction, a classical Mongolian medicine formula, is widely used to treat spleen deficiency diarrhea (SDD) in Mongolian for decades. Previously, the Caoguo-4 decoction volatile oil has been confirmed to be effective in ameliorating symptoms of spleen deficiency diarrhea in an animal model. However, the underlying mechanism of the Caoguo-4 decoction volatile oil is yet to be established. The aim of the current study was to investigate the antidiarrheal effects and mechanism of the Caog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The colonic epithelium of rats in the B group was intact and continuous, without inflammatory infiltration and structural damage. The colonic epithelium injury often occurs in chronic diarrhea rats (Mei et al, 2022 ). Our results showed that the integrity of the colonic epithelium in the M group was damaged.…”
Section: Resultsmentioning
confidence: 99%
“…The colonic epithelium of rats in the B group was intact and continuous, without inflammatory infiltration and structural damage. The colonic epithelium injury often occurs in chronic diarrhea rats (Mei et al, 2022 ). Our results showed that the integrity of the colonic epithelium in the M group was damaged.…”
Section: Resultsmentioning
confidence: 99%
“…Essential oils in Chinese medicine contain abundant active ingredients and demonstrate significant pharmacological activities in the nervous system, cardiovascular system, respiratory system, gastrointestinal system, etc. These oils also exhibit noteworthy antibacterial/antifungal, antiviral, anti-inflammatory, and anticancer effects . However, essential oils are prone to volatilization and oxidation when exposed to light, oxygen, and high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Spleen deficiency diarrhea is a prevalent gastrointestinal syndrome in clinical practice ( Ma et al, 2019 ; Shi et al, 2019 ). It is primarily caused by congenital endowment deficiency or prolonged illness, leading to weakness in the spleen and stomach, impaired digestion, and diarrhea ( Mei et al, 2022 ). Some literature has pointed out that the irritable bowel syndrome caused by weak spleen and stomach is as high as 57.5% ( Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%